The Scope of Newspaper as a Futuristic Medium for Publicity - Dr. K. R. Subramanian (International Journal of Engineering and Management Research, 2018)
The news paper as a medium for publicity and Advertisements is losing its luster and relevance in America and some western countries. But the same medium has shown remarkable growth in India. Circulation increased by more than 23 million copies a day between 2006 and 2016, according to a new report from India's Audit Bureau of Circulation. That's average growth of nearly 5% per year. Meanwhile, circulation came down in major Western countries including the U.S. (-3%), France (-6%), Germany (-9%) and the U.K. (-12%). Despite the strong growth of digital media in India, the traditional formats of television and print still account for the largest portion of total media ad expenditure. India remains somewhat unusual in that print revenues continue to grow, with newspapers specifically still serving as an effective way for advertisers to reach a significant audience. The research reports point out that newspaper growth was really coming from papers published in Hindi and in other local languages and dialects—generally referred to collectively as “vernacular” papers. English is used in India’s largest cities, leaving readers in smaller cities and rural areas with an appetite for content in their local languages. The scope of the present research paper is to identify reasons for this and futuristic scope for news paper as a medium for publicity.